2016
DOI: 10.1002/jso.24346
|View full text |Cite
|
Sign up to set email alerts
|

The surgical anatomy of the supraclavicular lymph node flap: A basis for the free vascularized lymph node transfer

Abstract: The pedicle length and diameter of the supraclavicular lymph node flap are suitable for a microvascular tissue transfer. J. Surg. Oncol. 2017;115:60-62. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In contrast, Gerety et al counted around 1.8 gross lymph nodes at the thoracodorsal donor site. 28 Similar lymph node counts of other donor sites have been reported, [29][30][31][32] whereas our study revealed a much higher number of lymph nodes. Differences in lymph node quantity of our study compared to others may be attributed to our dissection under 2.5 times loop magnification.…”
Section: Perfusion Studysupporting
confidence: 90%
“…In contrast, Gerety et al counted around 1.8 gross lymph nodes at the thoracodorsal donor site. 28 Similar lymph node counts of other donor sites have been reported, [29][30][31][32] whereas our study revealed a much higher number of lymph nodes. Differences in lymph node quantity of our study compared to others may be attributed to our dissection under 2.5 times loop magnification.…”
Section: Perfusion Studysupporting
confidence: 90%
“…Vascularized lymph node transfer has emerged as a relatively new physiologic procedure that brings functional lymph nodes into the affected site and restores lymphatic flow (Becker, Assouad, Riquet, & Hidden, ). Common donor sites for vascularized lymph node transfer include the inguinal (Becker et al, ; Clodius, Smith, Bruna, & Serafin, ; Gharb et al, ; Lin et al, ), axillary (Dayan, Dayan, & Smith, ), submental (Cheng et al, ; Patel et al, ), supraclavicular (Althubaiti, Crosby, & Chang, ; Steinbacher et al, ), and lateral thoracic (Batista, Germain, Faria, & Becker, ; Becker et al, ) regions. However, donor site morbidity remains a concern, including iatrogenic lymphedema, lymphorrhea, nerve injury, and conspicuous scar (Ciudad et al, ; Pappalardo, Patel, & Cheng, ; Patel et al, ; Sulo et al, ; Viitanen, Maki, Seppanen, Suominen, & Saaristo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Injury to this nerve can lead to asymmetries in facial movement, which are noticeable on opening the mouth, smiling, or grimacing. 46,47 In fact, Cheng et al report finding subtle asymmetries in $10% of patients in the early postoperative period following use of the submental VLN flap, although all cases resolve on their own without permanent nerve injury. 45 Furthermore, the pedicle length is short, which may require the inclusion of the facial vessels.…”
Section: Submental Flapmentioning
confidence: 99%